Utilizing Marine Biotechnology to Address Pollution in the Bay of Bengal, Bangladesh - Akhter, Shomaya; Akhter, Shomaya; Shohag, Sheikh; Alim, Md Abdul; Islam, Md Tohidul; Hossain, Mohammad Nazir (Bioresearch Communications, 2023)
Addressing marine pollution within Bangladesh's maritime boundaries through biotechnological methods is a vital undertaking in the battle against the environmental issues confronting this coastal nation. By harnessing biotechnology, creative solutions can be crafted to confront the various types of marine pollution, including plastic waste, oil spills, and chemical contaminants, which pose significant threats to the country's precious coastal ecosystems, biodiversity, and fisheries. These strategies employ agents for biodegradation, genetically modified organisms, and advanced filtration techniques to eliminate pollutants from aquatic environments and reinstate ecological equilibrium effectively. By integrating state-of-the-art biotechnological innovations with sustainable management practices, Bangladesh has the potential to safeguard its marine environment and ensure the lasting prosperity of its coastal communities and marine biodiversity. Bioresearch Commu. 10(1): 1432-1441, 2024 (January)